Envisioning the use of online tests in assessing twenty-first century learning: a literature review - Bopelo Boitshwarelo; Alison Kay Reedy; Trevor Billany (Research and Practice in Technology Enhanced Learning, 2017)
Abstract The digital world brings with it more and more opportunities to be innovative around assessment. With a variety of digital tools and the pervasive availability of information anywhere anytime, there is a tremendous capacity to creatively employ a diversity of assessment approaches to support and evaluate student learning in higher education. The challenge in a digital world is to harness the possibilities afforded by technology to drive and assess deep learning that prepares graduates for a changing and uncertain future. One widespread method of online assessment used in higher education is online tests. The increase in the use of online tests necessitates an investigation into their role in evaluating twenty-first century learning. This paper draws on the literature to explore the role of online tests in higher education, particularly their relationship to student learning in a digital and changing world, and the issues and challenges they present. We conclude that online tests, when used effectively, can be valuable in the assessment of twenty-first century learning and we synthesise the literature to extract principles for the optimisation of online tests in a digital age.